ANALISIS FRAMING BERITA PEMILIHAN UMUM PRESIDEN (PILPRES) 2014 PADA HARIAN UMUM SUARA PEMBARUAN (Studi Analisis Framing Zhongdan Pan dan Gerald M. Kosicki di Rubrik Laporan Utama Periode Mei-Juli 2014) - Christina Sandra N. Saputri; Yudha Asmara D.A (Fakultas Komunikasi, Sastra, dan Bahasa, 2015)
This study , to see news framing presidential election ( Election) 2014 Daily Voice Reform especially , in the main report rubric period from May to July 2014. News 2014 presidential election , is the most interesting news for the media and the public because of public interest . At election time , almost the entire media displays this news as hedline one Voice Daily Updates.This study , using descriptive qualitative method with the theory of framing analysis models Zhongdan Pan and Gerald M. Kosicki . This theory is used to analyze the 2014 presidential election reporting period from May to July in the main report section .The results of this study indicate that the news framing the 2014 presidential elections conducted by the Daily Voice Reform seen from the figure put forward the issue of its issue number 2 presidential candidate Joko Widodo ( Jokowi ) than the presidential candidate number 1 is Prabowo . Seen from the news headlines presented in the main report